2004
DOI: 10.1038/sj.jea.7500370
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-dependent TCDD elimination kinetics in humans: toxicokinetic modeling for moderately to highly exposed adults from Seveso, Italy, and Vienna, Austria, and impact on dose estimates for the NIOSH cohort

Abstract: Serial measurements of serum lipid 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) concentrations in 36 adults from Seveso, Italy, and three patients from Vienna, Austria, with initial serum lipid TCDD concentrations ranging from 130 to 144,000 ppt, were modeled using a modified version of a previously published toxicokinetic model for the distribution and elimination of dioxins. The original model structure accounted for a concentration-dependent increase in overall elimination rate for TCDD due to nonlinear distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 35 publications
8
105
4
Order By: Relevance
“…In linear regression adjusting for occupation, female sex was generally associated with higher serum concentrations for most compounds except for PCB#189, which was a pattern very similar to that observed for BMI. Although in New Zealand general population studies, serum concentrations of TCDD and other POPs have not been found to be different between men and women ('t Mannetje et al 2013), in a study of highly exposed individuals men had faster elimination of TCDD compared to women (Aylward et al 2005) which may explain our findings.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…In linear regression adjusting for occupation, female sex was generally associated with higher serum concentrations for most compounds except for PCB#189, which was a pattern very similar to that observed for BMI. Although in New Zealand general population studies, serum concentrations of TCDD and other POPs have not been found to be different between men and women ('t Mannetje et al 2013), in a study of highly exposed individuals men had faster elimination of TCDD compared to women (Aylward et al 2005) which may explain our findings.…”
Section: Discussioncontrasting
confidence: 47%
“…Given that the relationship between current serum measurements and 'actual' historical exposure is subject to inter-individual variations in elimination efficiency (Aylward et al 2005), and the elimination rate is also shown to be dose-dependent (Aylward et al 2005), our backcalculated TCDD exposure based on a single half-life for all participants is only an approximate indication of historical serum concentrations. Nevertheless, this study has shown that 20 years after production of 2,4,5-T had ceased, levels of TCDD and PeCDD were elevated in former workers from specific locations and occupations within the production plant.…”
Section: Discussionmentioning
confidence: 99%
“…In all, 30 of the 52 chlorophenol workers had 2,3,7,8-TCDD levels, which were higher than background found in this study of 6.0 ppt. We estimate that the mean level of 2,3,7,8-TCDD present in the serum of these 30 workers on the date workplace exposure terminated was 267 ppt (ranging from 8 to 1184 ppt) assuming a 9-year half-life, 582 ppt (ranging from 10 to 2641 ppt) assuming a 7-year half-life, and 1928 ppt (ranging from 22 to 17,847) when the toxicokinetic model proposed by Aylward et al (2005) is used.…”
Section: Resultsmentioning
confidence: 98%
“…The first method assumes a one-compartment first-order kinetic model with a half-life of 9 or 7 years (Flesch-Janys et al, 1996). The second method uses a recently developed toxicokinetic model elimination of 2,3,7,8-TCDD (Aylward et al, 2005). This model takes into account the concentration dependent elimination of 2,3,7,8-TCDD to the liver as well as the lipid partitioning from circulation into the large intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure estimation based on serum sampling data, work history records, and pharmacokinetic modeling has been used as a tool for assessing historical occupational exposures to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in workers involved in the manufacture of 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) (Ott and Zober 1996;Steenland et al, 2001;Crump et al, 2003;Aylward et al, 2005a). Because TCDD is highly persistent in human tissues, elevated exposures occurring many years before measurement in serum can be detected.…”
Section: Introductionmentioning
confidence: 99%